Protection of Persons in the Event of Disasters and Other Topics: The Sixty-Eighth Session of the International Law Commission. Issue 4 (October 2016) - Murphy, Sean D.
Abstract : The International Law Commission held its sixty-eighth session in Geneva from May 2 to June 10, and from July 4 to August 12, 2016, under the chairmanship of Pedro Comissário Afonso (Mozambique). Notably, the Commission completedonsecond reading a full set of eighteen draft articles with commentaries on the protection of persons in the event of disasters and recommended to the United Nations General Assembly that it elaborate a convention based on the draft articles. Additionally, the Commission adopted on first reading a complete set of draft conclusions, with commentaries, for two topics: identification of customary international law; and subsequent agreements and subsequent practice in relation to the interpretation of treaties. As such, both topics might be completed by the Commission on second reading in 2018. Progress was also made in developing draft articles on crimes against humanity; draft guidelines on protection of the atmosphere; draft conclusions on jus cogens ; and draft principles on protection of the environment in relation to armed conflicts. The Commission commenced a debate on a proposed draft article on "limitations and exceptions" to the immunity of state officials from foreign criminal jurisdiction, but, due to insufficient time, the debate will continue in 2017. Furthermore, an additional proposed guideline on the provisional application of treaties was sent to the drafting committee. The Commission decided to add two new topics to its long-term work program: the settlement of international disputes to which international organizations are parties; and succession of states in respect of state responsibility.